INFLUENCE OF COMPLEX PHYSIOTHERAPY ON THE FUNCTIONAL CONDITION OF THE SPINE IN OLDER PEOPLE - Sarzyńska-Długosz, Iwona; Jagieła, Magdalena; Pilis, Karol; Ptaszkowska, Lucyna; Pilis, Wiesław; Stec, Krzysztof (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of the present study was to assess the impact of 21-days comprehensive physiotherapy program on the functional condition of the spine and severity of pain in older people. To achieve this goal, physiotherapeutic procedures were performed on 100 elderly patients suffering from spinal disorders. The comprehensive therapy program consisted of: general improvement exercises, individual exercises with a physiotherapist, exercises in water and physical therapy treatments such as: TENS currents, galvanic current, iontophoresis, laser stimulation, magnetic field on the lumbar spine and hydro massage or mud compresses. Prior and post the therapy program: the Schober’s test - 1 (forward flexion), Schober’s test - 2 (extension), Ott’s test, fingertip-to-floor (FTF) test, pain Visual Analogue Scale (VAS) and the modified Oswestry low back pain questionnaire were evaluated. Statistically significant improvement (p<0.001) in all tested parameters was shown at the end of therapy program. Age, height, body weight and body mass index (BMI) has no impact on results before and after the physiotherapy program in respective tests. In conclusion, the conducted study has shown the effectiveness of applied comprehensive physiotherapy program on the functional condition of the spine and improvement of the quality of life of the treated patients, regardless of their somatic conditions.